Analysis Of Processing Development Strategy Peanuts In The Village Of Lagadi, District Of Lawa West Muna District - Lestina Lestina; La Rianda; Sakir Sakir (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2022)
This study aimed to determine the strategy for developing peanut processing in Lagadi Village, Lawa District, West Muna Regency. The population in this study were all peanut businesses in Lagadi Village, Lawa District, West Muna Regency, in 2020. Sampling was carried out by